Multi-factor identity authentication scheme for trusted sharing of cultural resources - Miaomiao WANG; Lanlan RUI; Siya XU (Tongxin xuebao)
To solve the problems of data leakage and identity impersonation caused by traditional single factor authentication, a multi-factor identity authentication scheme based on blockchain was proposed for the trusted sharing of cultural resources.Considering a variety of identity factors, a heterogeneous digital identity model was constructed using the tamper resistance and distribution of the blockchain distributed ledger.Through asymmetric encryption algorithm and exclusive OR (XOR) operation, the trusted reuse of heterogeneous digital identity and fast authentication of multi-agent access were realized.Security analysis and simulation results show that the proposed scheme outperforms existing multi-factor authentication schemes in terms of security and efficiency, and can effectively reduce the cost of identity authentication.